PENINGKATAN AKURASI INFORMASI LAYANAN SOSIAL MELALUI PENGEMBANGAN APLIKASI PEMETAAN TEMPAT SOSIAL MENGGUNAKAN API GOOGLE SERVICE - Cahyadi, Septian; Fairuz, Febri Damatraseta; Laurentia, Katarina Andrea; Mulia, Isnan; Pratama, Raihan Dwi (Jurnal Informatika Kesatuan, 2023)
Based on research results, even though technology is currently developing rapidly, complete data and information regarding social service providers in the regions are still difficult to obtain. The implementation of social service efforts in the regions often experiences obstacles due to a lack of communication facilities, as well as the lack of information on geographic location and information on the forms of social services available. This has resulted in uneven distribution of assistance received by social service providers in the regions. Therefore, we developed the Kasih Baik application which was developed using the spiral model System Development Life Cycle (SDLC) method. This method was chosen because it is the right model to use in prototype development. Kasih Baik itself is an application that consists of several main functions such as Tempat Kasih, Kasih Barang and Kasih Jasa. The purpose of this appendix is ​​to raise awareness of the public about registration and participation in the support of social services in the region, and to clarify the problems related to justice and improve the quality of justice services in the regions.